Preliminary Antibacterial and Phytochemical Assessment of Osmunda regalis L. - Thomas, Toji (International Journal of Pharmaceutical & Biological Archive, 2011)
Osmunda regalis is an important plant of traditional systems of medicine. Fronds (leaves) of Osmunda regalis were evaluated for its antibacterial potential and phytochemical contents in various solvent extracts of the plant in increasing polarity towards pathogenic bacterial species. Antibacterial activity was evaluated by disc diffusion method. Petroleum ether, acetone, methanol and water extracts of Osmunda regalis were tested for antibacterial activity towards some pathogenic bacterial strains. Both acetone and methanol extracts exhibited antibacterial activity; maximum activity was shown by acetone extract compared to others. Antibacterial activity was confirmed by minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC). MIC and MBC values of acetone extract of 12.5mg/ml and 25mg/ml were observed towards Pseudomonas aeruginosa while MIC and MBC values of 25mg/ml and 50mg/ml were observed towards Shigella sonnei. Flavonoids, phenols, steroids were detected in acetone and methanol extracts. The study proves that Osmunda regalis possesses antibacterial principles, soluble in acetone, which hinder the growth and multiplication of some multidrug resistant bacterial strains.